A Study of Success Rate of Miniscrew Implants as Temporary Anchorage Devices in Singapore - Song Yi Lin; Yow Mimi; Chew Ming Tak; Foong Kelvin Weng Chiong; Wong Hung Chew (International Journal of Dentistry)
Objective. To find out the success rate of miniscrew implants in the National Dental Centre of Singapore (NDCS) and the impact of patient-related, location-related, and miniscrew implant-related factors. Materials and Methods. Two hundred and eighty-five orthodontic miniscrew implants were examined from NDCS patient records. Eleven variables were analysed to see if there is any association with success. Outcome was measured twice, immediately after surgery prior to orthodontic loading (T1) and 12 months after surgery (T2). The outcome at T2 was assessed 12 months after the miniscrew’s insertion date or after its use as a temporary anchorage device has ceased. Results. Overall success rate was 94.7% at T1 and 83.3% at T2. Multivariate analysis revealed only the length of miniscrew implant to be significantly associated with success at both T1 (P=0.002) and T2 (P=0.030). Miniscrew implants with lengths of 10–12 mm had the highest success rate (98.0%) compared to other lengths, and this is statistically significant (P=0.035). At T2, lengths of 10–12 mm had significantly (P=0.013) higher success rates (93.5%) compared to 6-7 mm (76.7%) and 8 mm (82.1%) miniscrew implants. Conclusion. Multivariate statistical analyses of 11 variables demonstrate that length of miniscrew implant is significant in determining success.